Epidemiological characteristics and immune status of children with Respiratory Syncytial Virus - Ye, Qing; Shao, Wen-Xia; Shang, Shi-Qiang; Pan, Yan-Xiang; Shen, Hong-Qiang; Chen, Xue-Jun (Journal of medical virology, 2015)
Respiratory Syncytial Virus (RSV) infections are the dominant cause of pneumonia in children. In order to determine the epidemiological characteristics and immune status of children with Respiratory Syncytial Virus, a prospective study was performed among patients with RSV infection. Comparisons between RSV pneumonia group and normal control group, RSV pneumonia group had lower IL‐2 (median levels, pg/ml: 3.8 vs. 5.1, P < 0.01), and higher IL‐4 (median levels, pg/ml: 3.2 vs. 2.4, P < 0.01), IL‐10 (median levels, pg/ml: 12.2 vs. 2.3, P < 0.01), and IFN‐γ (median levels, pg/ml: 13.4 vs. 4.6, P < 0.01). The level of IgE among pneumonia patients caused by RSV increased sharply (median levels, mg/L: 48.1 vs. 8.8, P < 0.01). Another amazing finding is that after birth, the degree of IgE of the children infected by RSV increases gradually with age. This effect is at its peak in 0.6 years old. The IgE and eosinophil levels were higher when patients suffered from RSV pneumonia with wheeze (IgE median levels, IU/ml: with wheeze: 72.74 vs. without wheeze: 11.5, P < 0.05; eosinophil median levels, ×109/l: with wheeze: 0.21 vs. without wheeze: 0.05, P < 0.05). The main morbidity crowd is the children under the age of 1 year old. The downregulation of IL2 and the upregulation of IL‐4, IL‐10, IFN‐γ, and IgE happen after RSV infection. J. Med. Virol. 87:323–329, 2015. © 2014 Wiley Periodicals, Inc.